(untitled) (PETITUM, 2025)
This research analyzes the legal protection for creditors holding mortgage rights (Hak Tanggungan) over collateral objects declared null and void by the court, using Case Number 228/Pdt.G/2021/PN.Bpp as a study. The findings indicate that the court’s annulment of the mortgage object leads to the loss of the creditor’s right to execution, resulting in significant financial losses and legal uncertainty within the financing system. Required legal protection encompasses preventive measures through more rigorous collateral verification and repressive measures such as compensation mechanisms or collateral substitution. The study suggests a revision of Law No. 4 of 1996 on Mortgage Rights (UUHT) to clarify creditor protection when collateral is declared void by law, alongside strengthening the land verification system to prevent future legal defects. These steps are crucial to maintaining public trust in banking institutions and ensuring legal certainty for security interests.